Manfaat Aromaterapi Lavender Terhadap Penurunan Insomnia pada Lansia - Kusnanto Kusnanto; Harmayetty Harmayetty; Ira Suarilah; Ninuk Dian Kurniawati; Ulin Marliana (Universitas Airlangga, 2007)
Introduction: Insomnia is the primary sleeping problem experienced mostly by elderly. The objective of this study was to examine the effect of lavender aromatherapy for insomnia reduction in elderly.Methods: This study used pre-experimental design, with 15 samples, recruited by using total sampling. The independent variable was aromatherapy and the dependent variable was insomnia. Data were collected by using structured interview with questionnaire and observation. Data were analyzed by using Wilcoxon Signed Rank Test with significance level of p≤0.05.Results:The results showed that lavender aromatherapy given to elderly had beneficial effect on sleep quality and quantity of this age group. The sign and symptoms of insomnia become reduced with significance level of p=0.001.Conclusion: Lavender aromatherapy can be used as alternative intervention for overcoming insomnia in elderly.